Equipping Health Systems to Meet Older Adults’ Care Needs: A Novel Age-Friendly Patient and Family Advisory Council - Corrie Harris-Chunga; Timothy W. Farrell; Mari Ransco (Journal of Patient Experience, 2026)
As the older adult population continues to grow, health care systems must adapt their delivery models to meet this demographic’s specific needs. University of Utah Health is addressing this challenge by integrating the Institute for Healthcare Improvement’s 4Ms framework across its care continuum. This framework emphasizes What Matters, Medication, Mentation, and Mobility to support age-friendly care delivery for older adults. To support this integration, the Division of Geriatrics and the Patient Experience Department partnered in 2022 to launch a novel Age-Friendly Patient and Family Advisory Council (PFAC) comprised of older adults. During its inaugural year, council members shared personal care experiences framed around the 4Ms to help co-design organizational improvement initiatives. Analysis of the Age-Friendly PFAC sessions revealed three primary themes: the need for stronger patient-provider communication, a demand for individualized care strategies, and a recognition of the emotional complexities involved in the care experience. This research brief highlights the insights gathered from the sessions and outlines the development and implementation of the Age-Friendly PFAC, providing a scalable model for health systems looking to build their own councils.